Effect of the granular size on the zeolite content in the natural zeolite ores - Roumie , Akel; Husam Al-dien , Kawass; Saed, Ibrahim (Latakia University Journal -Basic Sciences Series, 2019)
Natural zeolite which named TS-14 from Tel- Asis area in Syria has beenstudied. The sample was crashed under fixed force, 5kg/cm2 and sieved with differentsizesieves. The product was divided to five samples with different size, andnamedTS-14-1,<0.125mm, TS-14-2, 0.125-0.3mm, TS-14-3, 0.3-0.6mm, TS-14-4, 0.6-85mm, TS-14-5, 0.85-1.4mm. The specific surface area was calculated. The maximum specific surface area was 84.6m2/g for the first sample which has minimum size, then the value of surface area decreases to become 54.2m2/g for the second sample, therefore the value of surface area increases for third and fourthsamples to became 60.3m2/g and 66.3m2/g, respectively. The adsorption of the Ni(II) ions was studied using the samples. The capacity of the samples is increasing when the granule size is increasing, and the maximum capacity was 91.7mg/g as Ni(II) ions for last sample. The adsorption process of Ni(II) ions takes place on the heterogeneous centers.